2009
DOI: 10.3168/jds.2009-2134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing amounts of supplemental progesterone in a timed artificial insemination protocol on fertility of lactating dairy cows

Abstract: The objectives were to evaluate the effect of supplemental progesterone during a timed artificial insemination (TAI) protocol on pregnancy per insemination and pregnancy loss. Lactating dairy cows from 2 dairy herds were presynchronized with 2 injections of PGF(2alpha) 14 d apart, and cows observed in estrus following the second PGF(2alpha) injection were inseminated (n = 1,301). Cows not inseminated by 11 d after the end of the presynchronization were submitted to the TAI protocol (d 0 GnRH, d 7 PGF(2alpha), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 25 publications
6
53
1
3
Order By: Relevance
“…Bisinotto et al (2013) observed that incorporating Bisinotto, Ribeiro and Santos 154 two CIDR inserts during the timed AI protocol for cows without CL increased concentrations in plasma to 2.65 ng/mL and restored fertility similar to that of cows in dioestrus when the timed AI was initiated. Similar findings had been observed by Lima et al (2009b) and Denicol et al (2012). Therefore, when supplemental progesterone has to be used in high-producing cows, it is suggested that benefits to P/AI will be greater when the resulting concentrations of progesterone in blood resemble those of cows in dioestrus and, in some cases, two intravaginal devices are needed to achieve such concentrations.…”
Section: Optimising Timed Ai Programmessupporting
confidence: 55%
See 1 more Smart Citation
“…Bisinotto et al (2013) observed that incorporating Bisinotto, Ribeiro and Santos 154 two CIDR inserts during the timed AI protocol for cows without CL increased concentrations in plasma to 2.65 ng/mL and restored fertility similar to that of cows in dioestrus when the timed AI was initiated. Similar findings had been observed by Lima et al (2009b) and Denicol et al (2012). Therefore, when supplemental progesterone has to be used in high-producing cows, it is suggested that benefits to P/AI will be greater when the resulting concentrations of progesterone in blood resemble those of cows in dioestrus and, in some cases, two intravaginal devices are needed to achieve such concentrations.…”
Section: Optimising Timed Ai Programmessupporting
confidence: 55%
“…The fact that the incorporation of a single progesterone insert to timed AI programmes improved P/AI in cows that lack a CL at the first GnRH injection, but not to reestablish fertility to the same level as those in dioestrus is likely related to the amount of progesterone released. The CIDR releases ∼90 mg of progesterone/day, which increases plasma concentrations in high-producing lactating dairy cows by ∼0.8 to 1 ng/mL (Cerri et al, 2009b;Lima et al, 2009b). Bisinotto et al (2013) observed that incorporating Bisinotto, Ribeiro and Santos 154 two CIDR inserts during the timed AI protocol for cows without CL increased concentrations in plasma to 2.65 ng/mL and restored fertility similar to that of cows in dioestrus when the timed AI was initiated.…”
Section: Optimising Timed Ai Programmesmentioning
confidence: 99%
“…With 30% and 35% OD and CR, respectively, combined programmes outperformed the TAI only programme with higher values at increased levels of OD. The study concluded that with a reasonable OD rates of 50% to 60% (Lima et al, 2009;Chebel and Santos, 2010), it would be recommendable to use OD only if the expected CR was greater than 30% (greater than the expected TAI CR). In agreement with previous findings (Giordano et al, 2011), that study also found that inseminating cows detected in oestrus before completion of a synchronisation protocol and expecting a low CR has a negative effect on the overall reproductive and economic performance.…”
Section: Od Synchronisation Programmes or A Combinationmentioning
confidence: 99%
“…The proportion of cows that remain anovular by 60 days postpartum ranges from 20% to 40% and can be as high as 60% (Lima et al, 2009 ). The severity and duration of negative energy balance postpartum is a major factor that infl uences ovarian activity and resumption of cyclicity postpartum in dairy cows.…”
Section: Body Condition Scores ( Bcs S )mentioning
confidence: 99%